2016
DOI: 10.21873/anticanres.11217
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Myoglobin Expression Is Associated with a Favourable Outcome in Head and Neck Squamous Cell Carcinoma Patients

Abstract: Abstract. Background/Aim: Ectopic myoglobin (MB)expressionMyoglobin (MB) is a cytoplasmatic monomeric oxygenbinding hemoprotein known to be localized mainly in cardiac myocytes and mitochondrial-rich skeletal muscles. In contrast to its relative haemoglobin, MB is only found in the blood stream after muscle injury. The functional paradigm of MB is the storage and intracellular transport of oxygen (O 2 ) (1, 2) to the mitochondria for oxidative phosphorylation within the myocyte. However, MB also maintains home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…The monomeric heme protein myoglobin is expressed predominantly in skeletal and cardiac muscles where it was believed to function solely as an oxygen reservoir, binding O 2 under aerobic conditions iScience Article and releasing it to mitochondria for cellular respiration under hypoxia (Galluzzo et al, 2009;Ordway and Garry, 2004). In recent years, the ectopic expression of myoglobin in non-muscle tissues as well as cancer cell lines and tumors has been reported (Bicker et al, 2020;Flonta et al, 2009;Kristiansen et al, 2011;Meller et al, 2016). Expression profiling of tumors from patients with head and neck squamous cell carcinoma has revealed that myoglobin expression is associated with better prognosis (Meller et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The monomeric heme protein myoglobin is expressed predominantly in skeletal and cardiac muscles where it was believed to function solely as an oxygen reservoir, binding O 2 under aerobic conditions iScience Article and releasing it to mitochondria for cellular respiration under hypoxia (Galluzzo et al, 2009;Ordway and Garry, 2004). In recent years, the ectopic expression of myoglobin in non-muscle tissues as well as cancer cell lines and tumors has been reported (Bicker et al, 2020;Flonta et al, 2009;Kristiansen et al, 2011;Meller et al, 2016). Expression profiling of tumors from patients with head and neck squamous cell carcinoma has revealed that myoglobin expression is associated with better prognosis (Meller et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory protein MB, known for its prominent presence in myocytes, is ectopically expressed in several cell types and malignancies, including tumors of the breast, prostate, lung, colon, kidney, bone, and head and neck (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic MB expression at a level of 1:100-1:1,000 compared to striated muscle was further reported in several tumor types, including breast, prostate, non-small lung and colon cancer, renal cell carcinoma, head and neck squamous cell carcinoma, osteosarcoma and leukemic bone marrow (18)(19)(20)(21)(22)(23)(24)(25). Instead of using the myocytic standard gene promoter, MB is transcribed from an alternative upstream promoter region in cancer cells, which can be specifically induced by hypoxia and silenced by hormonal treatments (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Mb is also found to be ectopically expressed in several cell types and malignancies, specifically in many epithelial-derived cancer cells including breast cancer [ 145 , [188] , [189] , [190] , [191] ], prostate cancer [ 191 , 192 ], non-small cell lung adenocarcinoma [ 193 ], renal cell carcinoma [ 194 ], head and neck squamous cell carcinomas [ 195 ], ovarian cancer [ 188 ], and colon cancer [ 188 ]. Mb expression status positively correlates with the overall survival rate of breast cancer patients [ 189 ], and patients with gleason score 8–10 prostatic carcinoma [ 192 ].…”
Section: Myoglobinmentioning
confidence: 99%